Babanki verb tone - Pius W. Akumbu (LibraryPress@UF, 2015)
In Babanki, a Grassfields Bantu language of northwestern Cameroon, several tonal patterns can be found on a single verb root depending on the construction in which the verb is used. An underlying high tone may surface normally as high, but unexpectedly as low, or high-falling; while underlying low tones surface as high, high-falling, or normally as low. For this reason the low tone verb can have a L(L), HL, or even H(H) surface melody while the high tone verbs can be L(H), HL, or H(H). Accounting for these melodies in order to reconstruct the underlying forms is necessary for a proper understanding of the Babanki verb tone in particular and the tonal system of Centre Ring Grassfields Bantu languages in general. This paper demonstrates that five tone rules (Downstep, Tone Docking, High Tone Spread, Low Tone Spread, and Upstep) and one phonological rule (Schwa Insertion) are required to account for the complex tonal system of Babanki verbs.